COVID-19 and professional dental practice. The Polish Dental Association Working Group recommendations for procedures in dental office during an increased epidemiological risk - Dominiak, Marzena; Różyło-Kalinowska, Ingrid; Gedrange, Tomasz; Konopka, Tomasz; Hadzik, Jakub; Bednarz, Wojciech; Matys, Jacek; Lella, Anna; Rayad, Sadri; Maksymowicz, Radosław; Kuźniarski, Amadeusz (Journal of Stomatology, 2020)
The recent spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and its associated coronavirus disease (COVID-19) has gripped the entire international community and has caused widespread public health concerns. Despite global efforts to control the disease transmission, the outbreak is still on a rise because of fast spreading of this infection by the community. Once in the human body, SARS-CoV-2 is abundantly present in nasopharyngeal and salivary secretions of affected patients, as it is predominantly transmitted through respiratory droplets and direct contact. Therefore, dental professionals may easily encounter a patient infected with SARS-CoV-2, and need to work with tremendous caution, preventing spreading of infection. Thus, the aim of this article was to provide a brief overview of epidemiology, symptoms, and routes of transmission of this novel infection. In addition, we present specific recommendations of the Polish Dental Association for dental practice for screening of patients, infection control strategies, and patient management protocol.